STUDI KASUS PENGGUNAAN QUIZIZZ TERHADAP MATA PELAJARAN IPAS KELAS V DI SDN SANTAKA - Ari Sujarwadi; Rizki Ramdani; Rico Mulyawan (STKIP Subang, 2024)
This research aims to analyze the use of the Quizizz platform as a learning medium in science subjects in class V at SDN Santaka. This research uses a case study approach involving students and teachers as research subjects. The main focus is to evaluate the effectiveness of Quizizz in increasing student learning motivation, understanding of the material, and active involvement in the learning process. Data was collected through observation, interviews, and analysis of student evaluation results. The research results show that the use of Quizizz has a positive impact on increasing students' learning motivation and understanding of science material. Apart from that, this application is also able to create an interactive and fun learning atmosphere. Thus, Quizizz can be an innovative alternative learning media to support the learning process in elementary schools.